Forrest gump - Hanks, Tom; Finerman, Wendy; Tisch, Steve; Starkey, Steve; Zemeckis, Robert; Paramount Home Video (Firm) (aHollywood, Calif. : Paramount Home Video, 2003)
Forrest gump is the movie triumph that became a phenomenon. Tom Hanks gives an astonishing performance as Forrest, an everyman whose simple innocence comes to embody a generation
Subtitles in English, Cantonese, Korean, Mandarin, Thai
Title from title screen
Director of photography, Don Burgess ; editor, Arthur Schmidt ; production design, Rick Carter ; music, Alan Silvestri ; screenplay by Eric Roth
Cast: Tom Hanks, Robin Wright, Gary Sinise, Mykelti Williamson, Sally Field
Keywords: Mentally handicapped -- Drama; Love -- Drama; Comedy films